Reporting police investigations, privacy rights and social stigma: Richard v BBC. Issue 2 (3rd July 2018) - Rowbottom, Jacob
ABSTRACT: In Richard v BBC, a media report revealing that the police were investigating a person in relation to alleged historic sex offence was found to violate the claimant's expectation of privacy. The ruling is important in drawing new boundaries on what can be reported in relation to criminal investigations. This article examines the decision and considers its relationship with other areas of law. In particular, the decision showed an overlap with defamation in so far as injury to reputation was central to the claim. More broadly, the law of privacy can now limit the publication of information about prior convictions, suggesting greater protection is now offered for personal information relating to the criminal justice system.